Interfaces Conference | Paul Dujardin (Onassis Foundation, 2020)
: Είμαι πολύ ευγενημένος που είμαι σήμερα στην Αθήνα. Επίσης, με τους παιδινούς μου, το αεροπλάνο δεν ήταν χαμηλό. Κάποιοι των Βελγιών έρθαν στην Αθήνα. Και με την ευγενία μου, με τον Παγκόσμιο, το αεροπλάνο δεν ήταν χαμηλό. Και με τον Παγκόσμιο, το αεροπλάνο δεν ήταν χαμηλό. Και με τον Παγκόσμιο, το αεροπλάνο δεν ήταν χαμηλό. Και με τον Παγκόσμιο, το αεροπλάνο δεν ήταν χαμηλό. Και με τον Παγκόσμιο, το αεροπλάνο δεν ήταν χαμηλό. Είναι η ασοσιακή μας στο κέντρο του ΦΑΝΑΡΤΑ, στο πρώτο μέρος, για να κάνουμε το έργο που κάνουμε τώρα για τόσο πολλά χρόνια. Πιστεύω ότι ήταν ενδιαφέρον να σας δείξω αυτήν την πρώτη σκέψη, γιατί είναι ένα εξαιρετικό σχολείο. Για αυτοί που δεν το είχαν δοκιμάσει, το δημιουργήθηκαν και συναντώθηκαν στο τέλος του 19ου αιώνα και το τέλος του 20ου αιώνα. Και πιστεύω ότι είναι σημαντικό, όπως αυτό το σχολείο εδώ, στην Αθήνα, σχετικά με, θα πω, το εξαιρετικό δυνατό της οικονομίας μας. Ίσως είναι το σχολείο που πιστεύει πιο αντι-ΒΑΟ, ή, θα πω, σχετικά με το φετισμό της αρχιτεκτήριας, που ήταν πολύ σημαντικό στη δεύτερη μορφή του 20ου αιώνα. Γιατί αυτό το σχολείο είναι δημιουργημένο μέσα από την πόλη, μεταξύ της πόλης και της πόλης. Βλέπετε εκεί, ένα σχολείο, σχολείο του Γενεράλ Μπελιάρ. Όλοι γνωρίζουν, στην Βρυξέλα, αυτή την αυλία, όπως εδώ, μεταξύ του κεντρικού κεντρικού και του Μπαμπιλόνου κεντρικού κεντρικού, στο άλλο πλευράδιο. Ελπίζω ότι το έχετε δει. Ο Μπαμπιλόν δεν ήταν τόσο μακριά από το Παγκόσμιο, 80 χιλιόμετρα, πιστεύω, από την Βαγδάτια. Η Βαγδάτια, όπως ξέρετε, ήταν ο κεντρικός κεντρικός της σχολείας και της κεντρικίας, πολύ πριν. Οπότε, δεν είναι νέο. Αυτό το προϊόντρο ήταν ένα δημιουργικό προϊόντρο, στο τέλος του 19ου αιώνα, σχετικά με το τι συνέβη στην Ευρώπη, σχετικά με την οικονομική ανάπτυξη στο πρώτο σημείο και σίγουρα με τη διεθνική ανάπτυξη. Στον κόσμο, όταν προσπαθούσαμε για τα τελευταία 150 χρόνια, δεν είναι η πολιτική που κάνει τη δημιουργία στην κοινωνία μας, στο πρώτο σημείο, τη διεθνική ανάπτυξη. Το βλέπουμε σήμερα όλον τον κόσμο και σίγουρα και στις ΗΠΑ, σχετικά με το κοινωνικό ανάπτυξη. Είναι σίγουρα λόγος της υψηλής ανάπτυξης της τεχνολογίας που κάνει ότι οι άνθρωποι φοβούνται για το μέλλον. Στο πρώτο σημείο, η διεθνική ανάπτυξη είναι σίγουρα η κυβέρνηση της αλληλεγγύης, πιο από τα οποία μπορούν οι πολιτικοί. Είναι σχετικά με αυτή την εμπορία. Ακόμα και σε αυτό το κέντρο, ήταν μια εμμονία του κοινωνικού τεχνολογίου L'Art Total, το Βοσάρ. Αν το Βοσάρ ανοίξε, ήταν πριν από την ΒΕΡΟΜΑ. Ήρθα από ένα χωριό της ΒΕΡΟΜΑ, όπως ο συναντός μου, Χριστόφ, σε ένα χωριό της Πασανδάλλης, πριν το 1915, πρέπει να γνωρίζετε ότι σε αυτό το χωριό, σε έναν μέρος, 27.000 άνθρωποι πήγαν σε έναν μέρος. Ήταν μια νέα πραγματικότητα, ότι οι σχέσεις μπορούσαν να καταστρέψουν το κόσμο. Με σχέση με το γαζό που χρησιμοποιούσαν στη ΒΕΡΟΜΑ. Με σχέση με αυτήν την πολύ σημαντική αλλαγή της ΒΕΡΟΜΑ, στο τέλος του 19ου και αρχής του 20ου αιώνα, με σχέση με την εξελίξη, θα επαναλαμβάνω μόνο ότι 85.000.000 άνθρωποι πήγαν στο ευρωπαϊκό κόντινετ, κυρίως στις Αμερικάνες. Και πιστεύω ότι υπάρχουν περισσότερο ΒΕΡΟΜΑ από την Ελλάδα, όπως γνωρίζετε, από την Ελλάδα. Και η αλήθεια και η αίσθηση που έχουμε για το μέλλον, σχετικά με αυτές τις πραγματικές πραγματικές, τα έχουμε αντιμετωπίσει σήμερα. Ο ΒΕΡΟΜΑ είναι ένα σημαντικό. Και αποφασίσαμε σήμερα να φτιάξουμε από αυτό το σπίτι ένα ευρωπαϊκό σπίτι για την πολιτική, σχετικά με όλα τα θέματα της δημοκρατίας, της ευρωπαϊκής πολιτισμίας, σχετικά με την πολιτική πληθυσία και τι σημαίνει αυτή η πληθυσία μας για το μέλλον. Και σίγουρα, σχετικά με το θέμα που συμμετέχουμε σήμερα, την ενοπλισμία, το διευθυμικό μέλλον. Υπήρξατε τη νέα μορφή για την Ευρώπη. Υπήρξαμε περισσότερες 3.000 ιντελεκτοί. Στην τελευταία συμμετέχωση, είχαμε δύο αλλητιστές. Η εξωτερική συμμετέχωση με τον Ιούνκο Ρενντουσκ δεν ήταν τόσο δημιουργητική αυτή η μορφή για την Ευρώπη. Αλλά αποφασίσαμε να δουλεύουμε, όπως μπορείτε να βρείτε στο ίντερνετ, το concept of cultural workers for Europe. And cultural workers for Europe was in the first place to redefine Europe, truly to its more democratic body and to find the necessary source to innovate and also to relate it to all these really challenges related to migration and also to the migrations who will come and the future diaspora. And I thought it was interesting to show this painting of the city hall of Siena. You know that at that time we had the Black Pest and we know that coming to the coronavirus in Siena they were building in that period a new church. And if you visit Siena you see that the cathedral is there by two walls but was never ended. But it was interesting that through the Black Pest who came from China, through Italy, all over Europe, took time, about four years, through all of Europe that 70-80% of European citizens died. And it's interesting to see that how in a city as Siena at the time, and we're coming back later in my speech about citizenship and the new cities of tomorrow, how it was in part to find already at that time, and I can only suggest if you go to Siena to go and see, it's about ten paintings, monumental paintings in a period of an alphabetism, how citizen participation was already very important at that time in Siena and how they were finding a balance between nature and the city and sophistication of a city life and at the same time the reality of the surrounding, in the reality of ecosystems. We had to live about security and how citizens could live together and the reality related to good and bad government, how citizens at that time in Siena were participating to forms of democracy where we tried to build for so many centuries in our old continent. And from that time, related to Beaux-Arts and this fundamental change, our art and science in the Weimar Republic of 1919 after the First World War, also related to Goethe, and we will see it later, but also early in 1919, there was this fundamental idea of art and science and that's the reason of the building of Beaux-Arts, to bring these both projects together in one house. Beaux-Arts is not a university, you have not this free space of an academic world, I'm not an academic, I'm not either a curator or an artist, but being director of Beaux-Arts, I thought it was important to come back to our origins and to recreate this Beaux-Arts lap. The most challenging thing for all of our arts institutions is not to have a lap like Ircam in the basement of the Centre Pompidou, as a beautiful metaphor, but to bring these in our institutions all over the place, in all the projects we try to do and not only in the periphery. So in the discussion of today, I will certainly refer to three main topics, the evolution of independency to interdependency. And second topic, the evolution from Renaissance to thinking to a more post-humanism. And third, the notion of perifical thinking to more collaborative practices. And that was also important in the way we went back to our origin, because that is related to three types of departments, the classical departments, still always fighting to bring these people out of their silos, the music, the literature, as its fantastic role written on this wall. And it's fascinating to see Athens in my regular visit of the last years, to see that a public space, the common, the open space of those attacks, that a new building on the seaside, in a popular area, a new library, is becoming such an important place here also in Athens today. How you bring art and science in a new situation. And for Beaux-Arts, it was important that we could bring together these disciplines in a vertical way, to get a more horizontal approach, a more holistic approach. And also the diagonal, where I will go more in detail, related to the SDGs, all the ethical debates we started in the 90s, we thought it was for the South-South debate, and that in the United Nations 2015, the Global Vision, it brought it more to a global vision of North and South. And so Beaux-Arts Lab is a reality today, many projects were realized, and all that related to the project we saw in the 20th century, like the labs in the public televisions, with all their projects, certainly related for the music world. I was referring to IRCAM, but I could even refer to mostly public radio and television stations, where the most famous artists from John Cage to Stockhausen, to more complex music, to minimalism, were working in these open spaces during the whole 20th century, while radio and then later public television and television were so fundamental to innovate during the whole 20th century. I'm referring to this impressive image already, because the historian Erik Opsbaum speaks about these ages of extremes. We always refer today to what's happening today in our society. Now, artists can be part of that debate of European Angst, knowing what will come. It's an impressive picture related to these gas attacks during the First World War. It's a very impressive image. It was using and the consequences of what happens in this postmodernism after the 80s, and sort of the memory to this 75th anniversary of the end of the Second World War. We were winning a second prize, I would say a special prize in Venice this year with the project Monde Carne. And interesting to know that related to these realities of the fairness and feel unfair treated, it's interesting to see if you go on the internet you will discover our project we did in Venice with Belgian artists from a cooperative workshop related to Monde Carne and the 3D printed puppets related to the world of the past. We see a reality that we try to imprison ourselves in the past and coming back to the old traditions, not anymore wishing to innovate. And in this world of polarization and extremism, I thought it was interesting to show this work of Jonas Lund related to the Cambridge analytics, related to how a populist as Trump, as you know, was winning the elections in working in this digital world. And Jonas Lund as an artist worked together with a Belgian company in innovation, Tel Aviv, and tries to see how also in the systems he was using, not only to use the fake news, but to bring complete other news, positive news about our society. And not only Jonas Lund was trying to give another message than the Brexit message, where we know later that finally the elite didn't vote and that we came to the Brexit. And even artists as Wolfgang Tillmann, famous artist living Berlin, artist living today in London, engaged himself certainly in that same debate when he was living in London and tried to do the whole debate of the Brexit to change to his artwork and his messages, to change the metaphor and influencing also the public opinion, what Trump did and again in these coming elections in the United States. It was interesting to see how he was trying to make the difference. And I think that's interesting to see how he unfortunately failed in his project. But again, it's interesting to discover that all artists are part of that debate. In these projects from the artist Anssi Polkinen, Street View, it's in front of the building Beaux-Arts, and it was just after the big migration crisis, we had most of the middle European countries after the First World War were firing their anniversary of independence. And related to the first topic of how we are independent and interdependent, and now we have this romantic idea of how we were increasing borders in the 19th century to create our national identities by creation of nations, this Finnish artist was showing this independence by bringing some results of a destroyed Syrian house. We had to bring all of the borders, negotiating with the different armies and the Turkish authorities to bring this work to Brussels and then finally to Helsinki. And it's showing really that this independence cannot exist anymore today. And we see it even in Belgium. During that First World War, as citizens decided to build Beaux-Arts, it was a citizen engagement to bring this project to reality after the First World War. It was an investment being a second economy, and it was, I would say, a lot before the larger foundations like the Onassis Foundation today and many other foundations in Europe and all over the world. It was an incredible project of 200 families who decided to build Beaux-Arts. And it's interesting to see that even Belgium was the second economy in the world when Beaux-Arts was built and trying to challenge us these same problems we challenge today. It's interesting to see that as an historian of economy, that in 100 years the Belgian economy was losing each year and that's why the reality of an European space, an European culture space related to an European economic space, is so fundamental in a globalized world and how artists related to these themes of independence are fundamental to work on these metaphors. And I thought that showing these rivers related to also our European system is an interesting... I don't know what's happened. It's interesting to see the European space and the rivers suddenly related to economic development and cultural development related to the low countries where I'm living and all over Europe, how culture is developing itself and how we know that delta regions all over the world will bring migration and migration to cities as we know more than 80% will go and live to these delta regions and how in these cities of tomorrow we will live. Fundamental works were done on that and it will be one of the big challenges of our society in this form of solidarity. And it's why I wanted to show this interesting presentation of the donut economy. I think you have already seen that the economist Kate Raworth made this fundamental presentation how you have to find a new balance between this ecological and social reality on which the arts world and more specific can be a part of the debate and to find the right balance in the whole discussion. We have to create a new form of living together in the 21st century and how we can make a balance of phosphorus future related to all these topics. I will not go in detail, but I think that it's important to keep that in mind and that engaged citizens can be part of that debate related to the European narrative and to make how technology is overwhelming our society. And we know that on that level the Silicon Valley policies, we have to give new answers on that level. Related to... I would first come back to a form of new renaissance. I was referring to this post-humanism of this drawing of da Vinci and I would relate immediately to 50, 50, 20, 1920 when Leonardo da Vinci is dying and that maybe one of the most famous artists just after da Vinci, Dürer, was visiting the Low Countries. He was travelling a lot and each time knowing the knowledge of the renaissance that leaving for sanitary reasons and health care when something happened in the cities, he had to leave and he was travelling around and coming to Brussels and I could only refer to a very famous book of McGregor on Germany, how this identity, European identity of artists where everything was centered to human beings was a fundamental development in the renaissance and coming back to this post-humanism where we need to find a new balance in our living together. And from this da Vinci reality, I'm coming to the organigram I found by the new site of Politico, how the Commission today tries to organize themselves and how from underneath the slide, the Commission is in charge of the geopolitical realities and more specific in the new Commission, how we have a new opportunity where Maria Gabriel, who was in charge for DigiConnect, all digital development, who is now in charge of Breton on the right side, Maria Gabriel will have and that's an opportunity for all of us in the debate of the coming day, is that she is in charge of education, Erasmus and the different programs we discussed, but at the same time, she is for the first time also in charge, replacing two men commissioners, she will be in charge of arising, not in 2020, but arising Europe and all research project and I thought it was important for us in these complexities to show these slides in which way the art world must be a part of that debate where the different opportunities will be, the digital world related to the new financial program will be about 80 billion euro in the coming years and how art and artists in the culture field can be a part of this discussion and in the center, I would refer to the joint research center, as you know, joint research center was the first research platform, agency of the commission, as you know, after the Second World War related to nuclear research and where Belgium was one of the leaders in the nanotechnology on security and measurement and still today, I think, if we want to come to a leadership worldwide in biotechnology, Belgium can be a part in the European Union in a form of solidarity in research coming to alternatives, to find solutions to all the big challenges and joint research center is situated in the six countries where found the fathers of the European Commission. I thought it's important to relate to an important center who was helping us a lot already for the last decades, it's Nesta. Nesta was one of the first really platforms in European Union certainly when UK became member of the European Union and that one for three years on the research is going to British universities and hoping that after the Brexit, these parts of brains will still be a big part of our common research inside European Union with the UK. But Nesta, with one of the professors of research, Francesca Bria, maybe you know her in different projects she was leading, was always showing how important art can be and how creative brains in innovation is so important to make the difference in our laboratory work today and that economic development will be very important. Here it's more relate to ethical thematics because she became, I think I lost one slide, Francesca Bria, today she became the advisor relate to ethical and digital innovation for the United Nations but for the recent years she was in Barcelona and I think it was interesting to see how somebody who came from the arts world and the culture world was appointed to be in charge of smart city policies in Barcelona and it's interesting to see what she did, if you go on the internet you will find more information how she worked on new systems to, I would say, a new form of governance for cities, countries and the world, how we can live together and I met her the first time in Alpach, it's interesting to see the Davos Alpach, these important places where politicians, economic business people come together and if you have documenta, Biennale of Venice is where the arts world is gathering, knowing that the Biennale of Venice was trying to make a Davos for culture but there's a big difference when you go to Davos, business people go there and pay for their travel and pay for their spendings. In Venice it was never working because you have to invite science and artists to come to these places and sadly enough many of these platforms were not always communicating but Francesca Bria is maybe one of these personalities who is building these bridges between messages and between how to implement and it was interesting to see how after the terrorist attack in Barcelona how she worked on data systems, not where we are different, you and me, she was working to bring data as a form of inclusiveness in our society and not to make police states where globally our digital realities are making new cities like in China where everything is related. I was in the main control room, not in China, recently in Seoul and it was very impressive to see and I was really shocked how these cities are working today and how freedom is becoming a real challenge to work on. So, interesting to follow this discussion of Nesta and the impact it can have on our work. The project that I boarded was a project we did with the Joint Research Centre in Beaux-Arts. It's for several years we try to bring these artists together and to see on a critical way with science people and artists bringing them together with all the good and the less good results but I think the last project we did in ISPRA, the largest centre of Joint Research Centre where we were collaborating on this using of data and the impact it has on our society. In this slide I think it's important to say that how an artist as Jonas Stahl, who is a Dutch, in all systems like in GIC, GIC, is transforming himself on the consequences of nuclear research related for example on earthquake situations where finally the periphery research has become the centre of the research and here Jonas Stahl is using and creating new alternative biospheres in old Reaktorenhalle, a former underground nuclear facility in Stockholm. And so he tries to create new alternative biospheres really to rethink and to create the debate. And it's interesting to see how in human, non-human reality visiting these places and related to a poetic approach between art and science and to create I would say not a space colonisation but a space corporation to create new metaphors in the world of I would say interplanetary alliances. It's interesting to discover. In the art and science of this post-human life it's interesting to see how I, as a Gawain in this project here, how the DNA can be manipulated and how it can be used in a way we know that we manage completely the DNA of humankind. How we have to challenge the ethical realities of two women if they would like to have a baby in a new, I would say in a new society, LGBT plus realities, having a child and how I could with my wife and with the DNA from a third part of a famous artist, I would say Luke Diamonds, if I would have a son who would be a good artist, how I can use and buy and that's a reality not on a new society of inclusiveness but a society of rich people with a new elite who could buy DNA to make and to realise new human bodies and it's interesting to create the debate on that project. Related to algorithms and the reality of ethical behaviour, I thought it was interesting to refer to the Neurons exhibition that Mathieu Cherubini organised in the centre of Pompidou. It's interesting to see how in a society where truck drivers and we will change, even in my region, in Flanders, where already the labour reality has completely changed, more than one million in a community of six million people will go on retirement, so there will be a real challenge of new labour and to reinvent our society, but not only technology but also thinking how we will use this technology in a new way of ethics and what can happen. Here it's a project on the way of accidents where the whole system of algorithms has to make decisions when an elderly woman would pass the street or there will be a child going, how the car will react, not in a way that artificial intelligence and already in a post-intelligence, because we are not speaking anymore from artificial intelligence, but already a more evaluated concept of that. And there we can see how artists have really specific skills to work with engineers on intuition, imagination, inspiration, storytelling, to make these things workable and to think on this future. On that level, the COP21 in Paris was interesting to see who Thomas Sarazeno, an artist living in Berlin, and who with his development of spiders, structures, can help to reorganise, to re-found the world. I saw his last exhibition, COP21 in Dusseldorf, was interesting that how, together with NASA, it can really bring solutions to society, the way that how data systems can work and to organise will better our society. And it's interesting to discover Thomas Sarazeno in his workshop. It's really when I visit these workshops, as Thomas Sarazeno or Olafur Eliasson or William Kentridge, really people where they bring in communities and working in this form of interdisciplinarity and intersectional approach where science artists are coming together to reflect. And that's interesting, related to that world of periphery. It's interesting to see that Humboldt, Goethe, Schiller, on this discussing about Kant, related to the Platon discussion already with Kant, is how we have this relation with nature. And certainly in these last 300 years, we had a long discussion. I think that in this thinking of the periphery, I would immediately come to this peripheral thinking that William Kentridge was developing in South Africa. It's interesting to see that for Europe as France, May 1968, everything was in Paris. And if you see an artist as William Kentridge who grew up in the 60s, 50s, 60s, 70s in South Africa, the reality of these social movements, new culture initiatives, was not only related to Paris, was related to, I would say, even the Soviet Union, the black movement in America, the reality all over Europe, even at Beaux-Arts, it was in May 1968, the place of revolution, and how we have these important shifts in our society and how we can have these discussions. And it's interesting to see how politicians also always relate to historical facts. But it's a reality today that we never had such an interesting reality. We can inspire ourselves to the past, but we have to look to the future. And here, I think it's interesting to see, one of my most inspiring artists is Michelangelo Pistoletto, who is 86 years old, is travelling all over the world still today, and really defending and creating still, I think, one of our main challenges of today, and most artists, like Olafur Eliasson, are inspired by the Arte Povera movement of Michelangelo Pistoletto after the Second World War. And it's interesting to see how he was referring to science with its infinity, the two first circles, and the first circle referring to nature. And what we was the basic of all, relate to the second circle, and Vitruvius and Leonardo da Vinci in the Renaissance, everything became artificial. We are in an artificial world today, even our relationships in all what we do in science, and already for a long time, Michelangelo Pistoletto came with a new form of configuration, where he added a third circle and his third paradise. Because mainly we were always thinking that there was always an end, that the world will be coming to an end, and it was more this apocalyptic idea of ending, where Michelangelo Pistoletto was giving really hope of a new future, a new renaissance, and he names himself Riberve. We made this project as an ambassador of this project. I think we did it all over the world, with kids, with students, in universities, we did it even in the European Parliament, as an aspect of imagination for a new generation, and finding a new balance between artifice and nature. It's important, related to this circularity, I give one example of Alexander Mankovsky, who is managing about 1,400 creative brains in a company as Mercedes himself. When he was in our workshop, I think he was never referring to a car. He's already in this post-mobility world of cars, but it's interesting to see how is his philosophy in the very traditional economy of the car industry of Germany, and where they need this in Europe, but certainly Germany in this industrialisation, come to a post-industrialisation, and we see very well how himself on the campus of the industrial site in Stuttgart, how he finds this new way investing with new brains to come to a new future, and how he brings these creative brains in innovation together, and to bring, I would say, a collective imagination between all these scientists, artists on the same platform, campus, from where we create new forms and new ideas. So, to end, I think it's important to note that Beaux-Arts, and there you see this building beside the bank, it's interesting to find in a new form of capitalism, where these 200 families were creating. It's important that Beaux-Arts is a part of a European network. We cannot be independent, as I said already. We can only make this project, and I think the European Union was stimulating that. I think that centuries in the periphery relate also to Greece and the reality of the discussion here and the solidarity that we need to have also in this new migration crisis that Greece is confronting. It's not a crisis of Greece, it's a crisis of Europe. I was a little bit shocked by the images of the leaders of the European Union looking from an helicopter to the border lines between Turkey and Greece, but it's an element of solidarity. It's a difficult answer to give, I think on that level also there, how we do the work on education related to these fundamental crises of migration and migration to cities. We know that 80% will go and live in cities, we know that in 2050 Africa will be doubled in numbers of inhabitants and in 2140% of the world community will be African. And that I saw recently 150 cities and commons in Germany asking against their national government that migration has to be embraced. So we have to find a new balance in this new way of policy. And knowing that Beaux-Arts is there trying to restore, to be open-minded, to create a more greater solidarity with the city where I'm living in in Brussels, the laboratory. In the area I'm living, around one square kilometre of my apartment, 186 languages are spoken. So this cosmopolitan reality where we have the fear of the other, how we can bring together that we want to live together in. And I think the middle was this idea of Gesamtkunstwerk from the Wiener Republik from 100 years ago. And I integrated that as a diamond. A diamond where we have this dialectic of where everything is coming together. And I think in a book we wrote with our staff the last four or five years, where would we go and in which way art centres, the Onassis Foundation, many other institutions, how we can create this solidarity between all these ways of working together and not any more to be in an interdisciplinary reality but in this intersectional reality of media, science, research and development and how we can have this solidarity of international cooperation. Why it was important to come to Athens and to have this discussion with you in the coming projects of the Commission and showing empathy, also a form of resilience of the form of what happens. I'm living less than one mile away of the most democratic body with the European Parliament. And what we have to show, and that's also, I need you in the work we have to do to these Members of Parliament. Even we cannot elect the best Members of Parliament because we have still not a federal all-over European system to create this new way. But I thought that it was important that we were part of the STARTS programme. We know that many universities worked on the STEAM and the STEM, where arts become a part, but I can say that my Brussels is the largest university city of Belgium with 65,000 students. And by the reopening of the academic year this year, there's a dropping of 50% of social science students for the last 10 years in Belgian universities. So the balance between social science and arts and philosophy is fundamental if we want to have a development of technology and at the same time, they need us and we need us. So in their STARTS, I must say, it's a small programme, it's an important programme with the other programmes that Europe was launching. And we hope that after the Brexit budget discussions, many countries want to reduce fundamentally the budget of art in the European policy. I think it will be a big error in strategy and policy. I thought that it was interesting to see how in this family company that you see here, Ottobock, a Berlin-based company, was one of the prize winners in Ars Electronica Linz. How important it is to find new balances in neurology, and the way that when a workman today would have this accident and have the arm, how you have to work on neurons related to digital world or flat screens and so on. And it's incredible how they made an incredible result. All the skin is related to the feeling of warm and cold and how the whole system is working. It's a fantastic realization from artists and engineers who work together in this project. To make a long story short, we had a big festival last weekend in Africa for the last 15 years. I'm involved and I can say that it's a big debate we will have for the coming years also all over Europe. You know that strange enough knowledge related to libraries and knowledge building, that strange enough, five, six countries wrote books we have in our libraries. And we have no books of intellectuals from Africa. And strange enough, they were the first printers of books before the printing started in the Renaissance in Europe. And so there is a really big debate related to the old colonizing countries where mainly Belgium, France, Germany, Spain, Italy, are the countries who had this experience. And in my capital, 45 million objects in the Natural Science Museum, the Africa Museum, are today related to the origins of Africa. And so I thought it was important in these border lines, in European space, in European participation, we need to embrace also this visionary Africa in the work we do. And we will start with the first Start Africa project. I refer also to Kigali, where Kagame brought together, it was in the New York Times two years ago, for the first time, a thousand scientists and artists to Kigali. And we did the master plan of the city of Kigali in the 25th anniversary of commemoration of the genocide. It was an important event where we brought 60 young architects to rethink the contemporary African city. So it's only a small part. We will be present in 12 weeks in Dakar, Biennale, related to the new Start Africa program. And Studiopia is the most recent project we will start on. And that's completely referred to my colleague Christophe Diago, who could tell more about that during the day tomorrow in our informal meetings. We will talk about how we are convinced that private companies need to embrace also, to connect with artists. And it's interesting to see that's not the way that artists have to go behind technology, but that is the other way round. We need to bring again engineers in the workplaces of artists. We did that with a lot of companies together with Christophe and his foundation Gluon, in which we are associated. And the results are incredibly interesting, how we connect these people on that level. And to end, I thought it's important to relate to next generation, please. It's a fundamental project I started several years ago when we do not understand anymore democracy, when it's too complex to know what is happening in the agora, in the place of encounters, when we need to speak about a language of how we live together. It's interesting to see that with young adults, we decided that we will translate these complex ideas on which we will discuss these days in images. And it's interesting to see how young adults, 16, 20 years old, together with politicians, and you can have Hermann von Rompuy, the former council president, is a Catholic conservative, with an artist who has completely other thought, but that you can see that independent and interdependent, even they have completely other views of society, that they can sit together between an artist, a scientist and a politician. And how they can be ambassadors in a dialogue with schools. And we studied it for the last five years, all the results. We connected with 100,000 students to embrace these new values, the values of our society, and to make and translate that in these images and artworks. And also to show these works in a museum place, in an art place. So the schools are not only art schools, all type of schools related where we did this work. And so I can end and conclude that Beaux-Arts tries to connect, and if we are here, is to have an open discussion on these different topics. I thank you.